In Vitro Evaluation of Neutral Aryloximes as Reactivators for Electrophorus eel Acetylcholinesterase Inhibited by Paraoxon - Kitagawa, Daniel A S; Cavalcante, Samir F de A; de Paula, Reuel L; Rodrigues, Rafael B; Bernardo, Leandro B; da Silva, Munique C J; da Silva, Thiago N; Dos Santos, Wellington V; Granjeiro, José M; de Almeida, Joyce S F D; Barcellos, Marcos C; de A Correa, Ana Beatriz; et al. (Biomolecules, 2019)
Casualties caused by organophosphorus pesticides are a burden for health systems in developing and poor countries. Such compounds are potent acetylcholinesterase irreversible inhibitors, and share the toxic profile with nerve agents. Pyridinium oximes are the only clinically available antidotes against poisoning by these substances, but their poor penetration into the blood-brain barrier hampers the efficient enzyme reactivation at the central nervous system. In searching for structural factors that may be explored in future SAR studies, we evaluated neutral aryloximes as reactivators for paraoxon-inhibited Electrophorus eel acetylcholinesterase. Our findings may result into lead compounds, useful for development of more active compounds for emergencies and supportive care.
Keywords: rybí proteiny; enzymové reaktivátory; antidotes; Enzyme Reactivators; Structure-Activity Relationship; molekulární struktura; Molecular Structure; Paraoxon; Fish Proteins; techniky in vitro; Oximes; neutral oximes; drug design; pesticides; acetylcholinesterase; acetylcholinesterasa; vztahy mezi strukturou a aktivitou; Animals; zvířata; oximy; Electrophorus; Acetylcholinesterase; paraoxon; In Vitro Techniques